1997
DOI: 10.1021/bi962598m
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inhibition of Amido Phosphoribosyltransferase from Mouse L1210 Leukemia Cells

Abstract: Amido phosphoribosyltransferase (amido PRTase) catalyses the first step of the pathway for de novo biosynthesis of purine nucleotides. The enzyme is subject to inhibition by purine nucleoside 5'-monophosphates (AMP, IMP, and GMP), by dihydrofolate polyglutamates, and by the antifolate piritrexim [Sant, M. E., Lyons, S. D., Phillips, L., & Christopherson, R. I. (1992) J. Biol. Chem. 267, 11038-11045). Using a coupled radioassay, we have determined the substrate dissociation constants as 80.4 +/- 13.2 microM for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Amido Phosphoribosyltransferase (APRTase, P-Rib-PP → PRA). APRTase catalyzes the first committed step of the de novo purine pathway (reaction 1, Figure ) and is inhibited by AMP, IMP, and GMP . The pentaglutamyl derivative of dihydrofolate and the nonclassical antifolate, piritrexim (Figure ), are potent inhibitors of APRTase in vitro .…”
Section: De Novo Purine Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Amido Phosphoribosyltransferase (APRTase, P-Rib-PP → PRA). APRTase catalyzes the first committed step of the de novo purine pathway (reaction 1, Figure ) and is inhibited by AMP, IMP, and GMP . The pentaglutamyl derivative of dihydrofolate and the nonclassical antifolate, piritrexim (Figure ), are potent inhibitors of APRTase in vitro .…”
Section: De Novo Purine Biosynthesismentioning
confidence: 99%
“…APRTase catalyzes the first committed step of the de novo purine pathway (reaction 1, Figure ) and is inhibited by AMP, IMP, and GMP . The pentaglutamyl derivative of dihydrofolate and the nonclassical antifolate, piritrexim (Figure ), are potent inhibitors of APRTase in vitro . De novo purine biosynthesis in mouse L1210 leukemia cells exposed to 1 μM methotrexate is blocked at reactions 1, 3, and 9, presumably due to inhibition of these enzymes by accumulated dihydrofolate polyglutamates .…”
Section: De Novo Purine Biosynthesismentioning
confidence: 99%
“…2,4-Diamino analogs of folic acid have been important in cancer chemotherapy. Despite its complexity, the underlying basis of cell growth inhibition by these compounds relies on their ability to block de novo synthesis of the purine nucleotides, i.e., precursors of DNA (Schoettle et al, 1997). This work is an extension of our previous study where we reported inhibition of amido phosphoribosyltransferase using 2,4-Diamino analogs of folic acid (Batool et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…10 mM, complete inhibition, sigmoidal inhibition curve, competitive vs. 5-phospho-a-d-ribose 1-diphosphate, GMP and AMP together have a synergistic effect on inhibition [3]; <3> 1 mM, approx. 40% inhibition [6]; <9> no inhibition in the presence of 5-phospho-a-d-ribose 1-diphosphate at high concentrations [7]; <6> 1.8 mM, 50% inhibition [8]; <6> 5 mM, 76% inhibition, noncompetive vs. glutamine [13]; <6> 5 mM, 79% and 24% inhibition of aminotransferase and amidotransferase activity at 1 mM 5-phospho-a-d-ribose 1-diphosphate [14]; <11> competitive vs. 5-phospho-a-d-ribose 1-diphosphate [16]; <10> 2.7 mM and 1.2 mM, 50% inhibition of stable and unstable enzyme preparation respectively [17]; <4> 5 mM, 50% inhibition [18]; <1> 4.7 mM, 50% in-hibition [19]; <7> competitive vs. 5-phospho-a-d-ribose 1-diphosphate, noncompetitive vs. glutamine [24]; <2> 50% inhibition of wild-type, S283A, K305Q, R307Q and S347A mutant enzyme at 0.9 mM, 6.1 mM, 2.5 mM, 2.6 mM and 1.5 mM respectively [25]; <13> 6.12 mM, 50% inhibition [28]) [1,3,6,7,8,13,14,16,17,18,19,24,25,28] ATP <6, 8> (<6> 5 mM, 21% inhibition [13]) [1,13] CMP <6> (<6> 5 mM, 22% inhibiiton [13]) [13] GDP <1, 3, 6, 8, 13> (<3> 1 mM, approx. 75% inhibition [6]; <6> 5 mM, 40% inhibition [13]; <13> 8.5 mM, 50% inhibition [28]) [1,3,…”
Section: Reaction Type Amino Group Transfermentioning
confidence: 99%
“…<5> Cricetulus griseus [10] <6> Homo sapiens [8,10,13,14,29] <7> Mus musculus [10,24] <8> Columba livia (pigeon [1]) [1,2,10,12] <9> Rattus norvegicus [1,7,10] <10> Schizosaccharomyces pombe (wild type strain 972hand mutant strain ade 2hdevoid of adenylosuccinate synthase [17]) [17] <11> Glycine max (soybean, Merr. cv.…”
mentioning
confidence: 99%